2017
DOI: 10.1109/tmi.2016.2641500
|View full text |Cite
|
Sign up to set email alerts
|

A Tensor B-Spline Approach for Solving the Diffusion PDE With Application to Optical Diffusion Tomography

Abstract: Optical Diffusion Tomography (ODT) is a modern non-invasive medical imaging modality which requires mathematical modelling of near-infrared light propagation in tissue. Solving the ODT forward problem equation accurately and efficiently is crucial. Typically, the forward problem is represented by a Diffusion PDE and is solved using the Finite Element Method (FEM) on a mesh, which is often unstructured. Tensor B-spline signal processing has the attractive features of excellent interpolation and approximation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…These truncated B-splines result in non-separable kernels. We refer the reader to [14,15] where an efficient method for the integration of such nonseparable kernels was proposed. Usually, the number of such kernels is small in comparison to the number of domain kernels.…”
Section: Operationmentioning
confidence: 99%
See 3 more Smart Citations
“…These truncated B-splines result in non-separable kernels. We refer the reader to [14,15] where an efficient method for the integration of such nonseparable kernels was proposed. Usually, the number of such kernels is small in comparison to the number of domain kernels.…”
Section: Operationmentioning
confidence: 99%
“…9, a) requires assembling a sparse matrix from B-spline kernels. It was shown that this approach appears to be the least efficient [14,15]. This follows from the overhead due to the sparse matrix format, from non-regular memory access, from a very low flop-to-byte ratio [21,22], and from problems concerning load imbalance [23].…”
Section: Ritz-galerkin Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence these discontinuous segments must be smoothed. B-spline curve is one of the most efficient curve interpolations and has been widely applied in many disciplines, such as medical imaging [27], geometric modeling [28], surface reconstruction [29] and position control [30]. With the properties of the B-spline curve, this interpolation scheme is practically useful for path smoothing [31], [32].…”
Section: Introductionmentioning
confidence: 99%